Three-dimensional gravity modelling of Kutch region, India. (1st January 2016) - Seshu, D.; Rama Rao, P.; Naganjaneyulu, K.
Graphical abstract: Highlights: First three-dimensional gravity models for the Kutch region, India. Mesozoic sediment thickness is more towards south of Vigodi and Katrol Hill Faults. Basement undulations are observed on Wagad Uplift. Crustal thickness varies from 32 to 45 km. Presence of fluids/melts/magma in the deep crust of Kutch region is negated. Abstract: Understanding the crustal architecture of Kutch rift region, India is important due to the presence of thick Mesozoic sediments and also due to occurrence of earthquakes. We present here three-dimensional gravity models. The major features of our shallow crustal model are: (1) thickness of Deccan Traps is almost negligible towards northern side of Vigodi Fault and Katrol Hill Fault (2) Mesozoic sediment thickness is about 3 km on the southern side and (3) several undulations in the basement on the Wagad Uplift. The model is consistent with the geological observation that the basin slopes towards southwest. The observed Bouguer gravity anomalies are explained by ∼10 km thick Granitic upper crust of 2.7 g/cm 3 ; ∼10 km thick intermediate mid crust of 2.82 g/cm 3 ; ∼15 km thick mafic lower crust of 2.91 g/cm 3 density. Crustal thickness is about 40–45 km on Wagad Uplift and near Katrol Hill Fault. The modelled gravity data do not require presence of anomalous amount of fluids, melts and/or magma chambers in the deep crust of Kutch region.